2016
DOI: 10.18805/lr.v39i6.6640
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic stresses alter expression of S-Adenosylmethionine synthetase gene, polyamines and antioxidant activity in pigeon pea (Cajanus cajan L.)

Abstract: Expression of S-Adenosylmethionine synthetase (SAMS) gene in pigeon pea (Cajanus cajan L.) was analyzed by qRT PCR during abiotic stresses viz., drought, heavy metal (CdCl 2 ) and cold. Maximum expression of SAMS gene in the leaves were observed at 3 days after drought stress with 15% PEG. Conversely, its expression was not detected in leaves and roots at cadmium stress but transcripts were down regulated as compared to the control. After 6 days of stress expression of SAMS gene was increased in leaves and roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…From the observation of our results, SAM seems to be up-regulated during cold stress (Table 2, Table S4). Studies of Guo et al [74], Mahatma et al [75], and Heidari et al [76] demonstrated that in plants such as Medicago sativa L. [74], Cajanus cajan L. [75], and Solanum lycopersicum L. [76], a gene encoding for SAMS was up-regulated in response to cold stress. Induction of SAMS during stress increases SAMS levels as positive effects of ethylene and polyamine biosynthesis [71].…”
Section: Cold Stress Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…From the observation of our results, SAM seems to be up-regulated during cold stress (Table 2, Table S4). Studies of Guo et al [74], Mahatma et al [75], and Heidari et al [76] demonstrated that in plants such as Medicago sativa L. [74], Cajanus cajan L. [75], and Solanum lycopersicum L. [76], a gene encoding for SAMS was up-regulated in response to cold stress. Induction of SAMS during stress increases SAMS levels as positive effects of ethylene and polyamine biosynthesis [71].…”
Section: Cold Stress Modelmentioning
confidence: 99%
“…Our results showed that regardless of the species subjected to abiotic stresses, the 12 genes analysed are involved in response to abiotic stress (Table S4). In fact, LHC-II was involved in plants such as tobacco and tomato in response to cold stress and SAM was involved in Medicago sativa L. [74], Cajanus cajan L. [75], and Solanum lycopersicum L. [76] (Table S3). [52]; HPT/AHP2 Histidine-containing phosphotransfer ABF [52]; OSCA1.1, Hyperosmolality-gated Ca 2+ permeable channel 1.1 [5,103]; OSCA1.2, Hyperosmolality-gated Ca 2+ permeable channel 1.2 [5,102]; OSCA3.1, Hyperosmolality-gated Ca 2+ permeable channel 3.1 [5,102]; AHA2, inhibition of the plasma membrane H + -ATPase 2 [52,104]; RALFs, Rapid alkalinization factors [5,105]; IPUT1, Inositol phosphorylceramide glucuronosyltransferase [5,106]; GIPC, Sphingolipid glycosyl insitol phosphorylceramide [5,106]; LLG1, co-receptor LORELEI-like GPI-anchored protein 1 [5,107,108]; LRX3, Leucinerich extension 3 [5,107,108]; LRX4, Leucine-rich extension 4 [5,107,108]; LRX5, Leucine-rich extension 5 [5,107,108]; SIP, RALF22 ligand via Site 1 Protease [5,109]; MYB, MYB-type transcription factor [110]; TCP, TCP-type transcription factor [110]; Class III HD-ZIP, Class III HD-ZIP transcription factor [110]; CBF-B/NF-YA, CCAAT-binding trans...…”
Section: Comparison Of Genes and Related Stressmentioning
confidence: 99%
“…Heavy metal stress induced the accumulation of Spd in Cajanus cajan (Radadiya et al, 2016) and of Put, Spm, and Spd in V. radiata (Choudhary and Singh, 2000). In G. max , the involvement of PAs seedlings response to cadmium stress was revealed by the induction of SAMDC after 3 and 24 h of Cd treatment (Chmielowska-Bąk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%